Analisis Implementasi Kebijakan Perlindungan Data Pribadi dalam Perdagangan Digital di Indonesia Berdasarkan eTrade Readiness Assessment - Muhtar, Tsuroyya Maulida; Radhiansyah, Emil (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2025)
Indonesia's digital economy is soaring, yet beneath the surface, a fragile data protection landscape threatens to undermine public trust and national security. This analysis critically examines the implementation of Indonesia's Personal Data Protection Law (UU PDP) 2022 by revealing a significant gap between legislative intent and effective execution. Despite rapid e-commerce growth, public awareness of data protection remains alarmingly low with over half of respondents exhibiting poor understanding. Drawing on UNCTAD's Multi-Stakeholder Consultations as the third stage of Indonesia eTrade Readiness Assessment, the study highlights persistent challenges consisting of weak law enforcement, fragmented regulations, and limited institutional capacity as evidenced by recurring major data breaches. A comparative analysis with Singapore, Malaysia, and South Korea further underscores Indonesia's lagging readiness in cybersecurity and data protection. The article argues that without comprehensive regulatory harmonization, institutional strengthening, and enhanced public education, Indonesia's ambition to become a leading digital economy will remain vulnerable and jeopardize both economic growth and digital sovereignty.